Peritoneal Mullerian Tumor-Like (Endosalpingiosis-Leiomyomatosis Peritoneal): A Hardly Known Entity - Rosa Bermejo; Alicia Gómez; Nuria Galiana; Antonio Campos; Rebeca Puente; Ernesto Bas; Carmen Díaz-Caneja (Hindawi Limited, 2012)
We describe a case of multiple peritoneal nodules with cysts at the free border of the omento and other locations of the peritoneal surfaces. A total abdominal hysterectomy and bilateral salpingooophorectomy were performed for a myomatous uterus and bilateral ovarian cysts. The omentum and several fragments of the abdominal peritoneum were also removed. Microscopic diagnosis was Disseminated Peritoneal Endosalpingiosis-Leiomyomatosis.